2017
DOI: 10.5812/jhealthscope.62595
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Volatile Organic Compounds at Petrochemical Complexes in Iran

Abstract: Background: The operation of petroleum refineries and petrochemical plants is associated with the emission of organic compounds into the atmosphere, causing local and regional pollution that is harmful to people's health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…Workers in their workplace can be potentially exposed to a wide range of harmful occupational factors, including chemicals (dust, gases, and vapors), physical hazards (noise, ionizing radiation, and inappropriate weather conditions), and psychological and ergonomic factors (stress and high mental workload). Exposure to these agents can cause a variety of occupational complications and diseases in workers, such as respiratory diseases, musculoskeletal disorders, physiological disorders, and cancers (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…Workers in their workplace can be potentially exposed to a wide range of harmful occupational factors, including chemicals (dust, gases, and vapors), physical hazards (noise, ionizing radiation, and inappropriate weather conditions), and psychological and ergonomic factors (stress and high mental workload). Exposure to these agents can cause a variety of occupational complications and diseases in workers, such as respiratory diseases, musculoskeletal disorders, physiological disorders, and cancers (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…This retrospective cohort study was counducted in the Iranian petrochemical complex, consisting of 10 re nery and 15 petrochemical plants, in one of the largest industrial sites in the Middle East. Therefore, all workers in this industrial area will, to some extent, experience exposure to toxic chemicals in their work environments (22,23).…”
Section: Participantsmentioning
confidence: 99%
“…Re nery workers have been reported to be exposed to toxic gases in the workplace (4,12,22), which has raised attention towards exposure assessment and health effects in this occupational group. However, long-term monitoring of exposure to SO 2 , NO 2 , O 3 , H 2 S and ammonia (NH 3 ) has, to our knowledge, not been examined in relation to objectively assessed spirometric parameters among petrochemical workers.…”
Section: Introductionmentioning
confidence: 99%
“…Among VOCs, BTEX (benzene, toluene, ethylbenzene, and xylenes) compounds are of the most environmental concern. They are a prerequisite for the formation of photochemical oxidants 8 and linked environmental effects, like formation of the tropospheric ozone, global warming, photochemical smog, and stratospheric ozone depletion 7 . Exposure to VOCs might be harmful to humans as they cause leukemia and adverse effects on the liver, nervous system, heart, and kidneys 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal variations may change concentration patterns and peak time of pollutant occurrence 27 . Also, pollutant concentrations vary regarding the tasks performed by workers in the particular workstations 8 . Based on literature review we found out that majority of the available studies did not consider the impact of seasonal variations and concentration changes of investigated pollutants among various workstations during performing human health risk assessment.…”
Section: Introductionmentioning
confidence: 99%